The Effect of Organizational Innovation Climate on Employee Innovative Behavior: The Role of Psychological Ownership and Task Interdependence - You, Yutian; Hu, Zhongfeng; Li, Jiawei; Wang, Youhan; Xu, Mingli (Frontiers in Psychology, 2022)
In today’s era of rapid development of science and technology, organizations are confronted with unprecedented opportunities and challenges. Employee innovative behavior becomes the key element to promote organizational innovation and achieve sustainable competitive advantages. This study examines the relationship between organizational innovation climate and employee innovative behavior by focusing on the mediating role of psychological ownership and the moderating role of task interdependence. The survey data was collected from the matched samples of 326 employees and their direct supervisors from 13 enterprises in Guangdong Province, China. The results indicate that organizational innovation climate is positively related to employee innovative behavior, and that psychological ownership plays a full mediating role between them. For the moderating effects, task interdependence positively moderates the relationship between organizational innovation climate and employees’ psychological ownership. The results also reveal an indirect effect of organizational innovation climate on employee innovative behavior through psychological ownership. Theoretical and practical implications are also discussed.